IS-mediated loss of virulence by Aeromonas salmonicida: A tangible piece of an evolutionary puzzle - Tanaka, Katherine H. (Landes Bioscience, 2013)
Insertion sequences (IS) are abundant in the bacterial fish pathogen Aeromonas salmonicida genome. IS are involved in rearrangement events that lead to the loss of virulence. In previous work, we studied a plasmid rearrangement that causes the deletion of the type three secretion system in A. salmonicida, resulting in a loss of virulence. We showed that the rearrangement is caused by the recombination of two IS (ISAS11) on an unstable plasmid (pAsa5). However, many rearrangements cannot be explained by our experimental approach and are thought to be the result of more complex or incomplete rearrangement events, as suggested by other plasmid loss profiles observed in various A. salmonicida strains. In this commentary, we examine the genetic instability of A. salmonicida indicating that its genome is rapidly evolving.